Needle Driver Control for a Robotic MIS Suturing System. Issue 9 (2021) - Shen, Kuan; Yen, Jia-Yush; Kang, Hao-Xiang; Ho, Ming-Chih; Chen, Yung-Yaw
Abstract: Autonomous robotic suturing has attracted research attention for years. Few results have shown the performance of an integrated robotic arm with a needle driver. This research introduces a coupling mechanism to connect a Da Vinci® large needle driver to a six-axis robotic arm. The motion of the needle driver wrist is treated as two additional motion degrees-of-freedom for the robot to simultaneously maintain the remote center-of-motion (RCM) and the needle path. The experiment employed the augmented state approach for the RCM generation and formulated the desired needle trajectory into the task control framework. This framework enables the implementation of a common robot controller. A trajectory correction procedure is also introduced to correct for the error resulted from the wrong gripper dimensions. With the proposed system, the experimental results on a training phantom show a successful tracking of the predefined suturing path.